Identification of underlying and transfusion-related platelet qualitative alterations in the hemato-oncologic patient. Issue 5 (October 2017) - Vicente-Ayuso, Carmen; Papadopoulos, Petros; Villa-Fajardo, María; Prieto, Blanca; Álvarez-Carmona, Ana María; Mateo-Morales, Marta; Pérez-López, Cristina; Peña-Cortijo, Ascensión; Polo-Zarzuela, Marta; Sáez, Isabel; Martín, María Paz; Benavente-Cuesta, Celina; et al.
Abstract: Hemato-oncologic patients with chemotherapy-induced thrombocytopenia are one of the populations receiving platelet transfusions. The general practice with these patients is to give prophylactic platelet transfusions when platelet counts fall below 10 × 10 9 PLT/L. However, in more than 40% of these patients, platelet transfusion does not prevent bleeding. The reason of the low efficacy of platelet transfusion in the context of chemotherapy patients is not entirely understood. We therefore aimed at immunophenotyping the expression of platelet surface and activation markers and thrombopoietin levels from hemato-oncologic patients before and after transfusion. A more detailed follow-up was performed in three patients that underwent autologous bone marrow transplantation. As previously reported, basal platelet activation was observed in hemato-oncologic patients. Based on flow cytometry parameters, i.e. the percentage of positivity and mean fluorescence intensity (MFI) distribution, our data provide an additional interpretation of platelet acquired qualitative changes in the hemato-oncologic patient. From our results we propose: first, the underlying activation of platelets in the hemato-oncologic patient is accompanied by loss of expression of the platelet receptors that are susceptible to protease-mediated shedding; second, soon after transfusion, the newly circulating donor platelets show additional activation, which may result in subsequent platelet receptor recycling and potential accelerated clearance of these activated platelets. In conclusion, the immunophenotype of circulating platelets changes after prophylactic platelet transfusion. Next to platelet count increment, exploration of this immunophenotype might help to explain transfusion refractory bleeding in hemato-oncologic patients. Eventually this may lead to personalization and improvement of the present platelet transfusion support regime.